Pengaruh Promosi Promosi dan Gratis Biaya Pengiriman Terhadap Keputusan Pembelian Masyarakat Nagan Raya di Marketplace Shopee - Marwan, Marwan (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Technological development has significantly transformed consumer shopping behavior, particularly through the increasing use of online marketplaces such as Shopee. Various promotional strategies—especially discounts and free shipping—are believed to influence consumer purchasing decisions. However, the extent to which these strategies effectively affect consumers’ purchase decisions requires empirical investigation. This study aims to analyze the influence of discount promotions and free shipping on the purchasing decisions of consumers in Nagan Raya Regency on the Shopee marketplace. This research employed a quantitative descriptive method with a total sample of 96 respondents selected using Cochran’s formula. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, descriptive analysis, classical assumption tests, and multiple linear regression using SPSS. The findings indicate that both independent variables—discount (X1) and free shipping (X2)—have a positive and significant influence on purchasing decisions (Y). The partial t-test revealed that discounts significantly affect purchasing decisions with a t-value of 5.655, while free shipping also shows a significant influence with a t-value of 7.814. The simultaneous F-test produced an F-value of 152.158 with a significance of 0.000, showing that both variables jointly influence purchasing decisions. The study concludes that higher discount offers and easier access to free shipping significantly increase the likelihood of consumers making a purchase on Shopee. These promotional strategies are proven effective in enhancing consumer purchasing decisions and may serve as valuable insights for businesses in formulating more targeted digital marketing strategies.